Work autonomy and its associated factors among nurses working in South Gondar zone public hospitals, Amhara regional state, Northcentral Ethiopia: Institution-based cross-sectional study - Yirgalem Abere; Abraham Tsedalu Amare; Astewle Andargie Baye; Yeshiambaw Eshetie; Demewoz Kefale; Gebrehiwot Berie Mekonnen; Gebrie Kassaw Yirga; Mengistu Ewunetu; Masresha Kassaw Ewinetu; Bekalu Mekonen Belay (PLoS ONE, 2026)
Background Work autonomy is crucial for nurses, which allows nurses to use their expertise and understanding of the profession to make informed decisions about patient care. However, research on nurses’ work autonomy is limited, particularly in low-income countries like Ethiopia, which is the focus of this study. Objective This study aimed to assess the level of work autonomy and its associated factors among nurses working in public hospitals in the South Gondar Zone, Ethiopia. Methods A cross-sectional study was conducted in public hospitals of the South Gondar zone from January 12 to February 20, 2024. The data was collected through a self-administered pretested questionnaire. The collected data were entered into EpiData V.4.2 and then exported to SPSS V.25 for analysis. The statistical significance of the association between outcome variables and independent variables was declared at a P-value less than 5% (0.05) at 95% CI. Results The overall level of good work autonomy among nurses was 53.5% (95% CI: 53.32–53.78). Factors significantly associated with good work autonomy include receiving on-the-job training (AOR = 1.6; 95% CI: 1.0–2.5), having five years of work experience (AOR = 1.9; 95% CI: 1.1–3.2), being bothered by lack of materials (AOR = 1.8; 95% CI: 1.1–3.0), and wishing to stay in the nursing profession (AOR = 1.8; 95% CI: 1.1–3.1). Conclusion While over half of nurses reported good work autonomy, critical barriers such as insufficient resources and intent to leavethe nursing profession hindered optimal autonomy. Enhancing nurse autonomy through targeted training and improved work experience is essential to advancing nursing practice and healthcare outcomes in the region.